Time Series Analysis of the Foreign Direct Investment in Nepal: Economics Perspective - Koirala, Dhirendra Prasad; Abdullah, Nazirdduin (Journal of Advanced Academic Research, 2023)
The main aim of this paper is to identify the major economic determinants of foreign direct investment in Nepal. In doing so, the Johansen-Juselius (JJ) cointegration approach as well as vector error correction model are implemented to identify the relationship among the macro variables. The empirical results revealed that all the variables are stationary at first difference and the evidence of cointegrating vector is obvious based on the JJ cointegration results. In addition, it is found that there is a long run relationship among the variables based on the coefficient of Error Correction Term (ECT). The long run coefficients show that Trade, GDP, exchange rate, and interest rate have a positive impact on FDI in Nepal, while, gross fixed capital formation (GFCF) and inflation (CPI) have a negative impact. Finally, in the short run, only one lag of FDI is affecting FDI. These results suggest that the inward FDI tends to incorporate information from the macroeconomic variables.